ANALISIS PEMBELAJARAN BAHASA INDONESIA DALAM MEMBANGUN KEMAMPUAN LITERASI MEMBACA PADA SISWA KELAS IV SDN LABANG KABUPATEN BANGKALAN - Argatya Abid Nur Fadhlurrahman; Muyessaroh, Aris; Rania, Nabila Putri; Muyessaroh, Asri Istiqomaturrobiah; Danu Pratama Putra; Ahmad Sudi Pratikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe students' literacy level in Indonesian language learning. The research method used was descriptive qualitative research. The research subjects included fourth grade students and teachers. The population of this study was 34 students with 17 male students and 17 female students in grade IV. Data collection techniques used observation, questionnaires, and interviews, while the research instruments used observation sheets, questionnaire sheets, and interview sheets. The results of this study were that there were 6 students who could read fluently, 26 students who could read but not fluently, and 2 students could not read.